Influence of husbandry practices on endoparasitism and evaluation of anthelmintic resistance on small ruminant farms in Selangor and Negeri Sembilan - Chai, Aiting (2015)
The study was conducted to investigate the influence of selected husbandry practices on endoparasitism in small ruminants as reflected by strongyle faecal egg counts. The anthelmintic resistance of gastrointestinal strongyles on a farm was also determined. Faecal examination of six small ruminant farms was conducted at farms of Ladang Angkat, Faculty of Veterinary Medicine, UPM. Faecal samples were collected from 40 small ruminants from each farm and subjected to the Modified McMaster technique for determination of faecal egg count (FEC). A standardized questionnaire was directed to the six owners to obtain information on selected husbandry practices adopted on their farms. The FEC was higher in the farm that allowed its animals to graze compared to the non-grazing farms. The farm that used its goat manure to fertilize its pasture had relatively higher FEC compared to farms that sold off its animal manure. Farms that used improved grasses as feed had goats with better body condition score than the farm that allowed its animals to graze on native grasses. However the better nutrition afforded by the improved grass was negated by concurrent diseases and dirty water source present in two farms. The Faecal Egg Count Reduction Test (F.E.C.R.T) was conducted in a farm whose animals had high FEC to determine anthelmintic resistance. The anthelmintics used in this test were albendazole, ivermectin, closantel and levamisole. Results of percent FEC reduction indicated that the strongyle population in that particular farm showed resistance to albendazole, ivermectin and closantel. However, susceptibility of the strongyles to levamisole was evident. Identification of infective larvae derived from faecal culture indicated that the major strongyle specie on these farms was Haemonchus contortus.